2019
DOI: 10.1080/13880209.2019.1657907
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycaemia and related gene expressions of aqueous extract ofGongronema latifoliumleaf in alloxan-induced diabetic rats

Abstract: Context: Gongronema latifolium Benth (Asclepiadaceae) has been highly utilized in controlling diabetes mellitus traditionally in the eastern part of Nigeria.Objectives: Antihyperglycaemic and related gene expressions of aqueous extract of Gongronema latifolium leaf in alloxan-induced diabetic rats.Materials and methods: Forty-eight female Wistar rats were induced intraperitoneally using alloxan (150 mg/kg body weight). The rats were separated into six groups (n = 8) as follows: non-diabetic control, diabetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…In another word, diabetic animals showed a reduction in cardiac GSH, designating its excessive usage in the redox-tackled cellular vicinity 19) . SOD, an enzyme involved in the dismutation of superoxide, CAT and GPx are enzymes that catalyze the breakdown of hydrogen peroxide (free radical) to water and oxygen 20) , and GST is a detoxification enzyme that functions in safeguarding cellular macromolecules from attack by reactive electrophiles 2) . The levels of all these (enzymatic and non-enzymatic) were noticeably increased in diabetic animals treated with the two doses of ST leaf, which were drastically reduced in diabetic rats, supporting their roles in scavenging the generated ROS due to STZ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another word, diabetic animals showed a reduction in cardiac GSH, designating its excessive usage in the redox-tackled cellular vicinity 19) . SOD, an enzyme involved in the dismutation of superoxide, CAT and GPx are enzymes that catalyze the breakdown of hydrogen peroxide (free radical) to water and oxygen 20) , and GST is a detoxification enzyme that functions in safeguarding cellular macromolecules from attack by reactive electrophiles 2) . The levels of all these (enzymatic and non-enzymatic) were noticeably increased in diabetic animals treated with the two doses of ST leaf, which were drastically reduced in diabetic rats, supporting their roles in scavenging the generated ROS due to STZ.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a metabolic malady tagged with persistent hyperglycemia resulting in instabilities of carbohydrate, protein, and lipid metabolisms because of flaws in insulin secretion, insulin action, or both 1) . This triggers a series of clinical signs such as polyuria, polydipsia, polyphagia, and abnormal weight loss, amongst others 2) . Currently, more than 422 million people are suffering from this disease globally, with a death rate of over 4 million each year 2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glide) to find the best ligand that fits into the binding pocket of a receptor at the atomic and sub-atomic levels, thereby simulating intermolecular interaction between them [21,22]. Recent studies have shown the antidiabetic properties of Gongronema latifolium in rat model [23][24][25]. In order to investigate the binding capacity of the bioactive compound in Gongronema latifolium leaf on proteins related to diabetes in humans, the fractions of Gongronema latifolium leaf consisting of different phytochemicals were docked with fifteen protein targets associated with type 2 DM to discover the possible hit compounds.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…1 Recently, there has been an increase in plant-based therapeutic products in both developed and developing countries because they are mostly non-toxic, have fewer side effects, and are available at affordable prices. 2,3 One such medicinal plant is Gongronema latifolium. The plant belongs to the family of Asclepiadacae.…”
mentioning
confidence: 99%